Anticholinergic Drug Burden in Older People's Brain – How well is it Measured?. (19th October 2013) - Kersten, Hege; Wyller, Torgeir Bruun
Abstract Concurrent use of several drugs with potential anticholinergic properties is highly prevalent in the elderly. Methods to determine the overall anticholinergic drug burden have been developed to estimate the risk of central anticholinergic adverse effects. The objective of this MiniReview was to critically appraise the clinical utility of the methods used to assess the anticholinergic drug burden in older people's brain. We evaluated the in vitro method used to measure the anticholinergic activity in a patient's serum and the four anticholinergic drug scales: Anticholinergic Risk Scale, Anticholinergic Cognitive Burden, Drug Burden Index and Anticholinergic Drug Scale. Medline searches of the literature from January 1988 to January 2013 were performed. Studies that related anticholinergic drug burden to central adverse outcomes in elderly people were included, while case reports and studies of single substances were excluded. Despite the consistently reported association between a high anticholinergic drug burden and negative cognitive and psychomotor outcomes in older patients, there are discrepancies in the literature. Furthermore, no significant cognitive improvements after the anticholinergic drug burden was reduced have been shown in randomized controlled trials. It is reasonable to question whether the estimated anticholinergic drug burden can predict the overall brain effects of multiple anticholinergic agents in older people.